International sale of goods regimes : the making and expected arrival of a shari'ah compliant model law / Sharifah Saedah Syed Mohamed - Sharifah Saedah , Syed Mohamed (2013)
The study of international trade law involving an international sale of goods typically comprises of at least four documents. They are the contract of sale, the contract of carriage, the contract of insurance, and the financing arrangements with banks or financial institutions to facilitate payment for the goods purchased. The key features of international trade are, inter alia, to render certainty in the parties’ rights and obligations by ensuring that the law is consistent and predictable; to provide sufficient flexibility to the parties’ needs to do business by permitting the recognition of trade customs and usages and also to recognise the international dimension of commerce by the application of specialised rules of conflict of laws, the admission of practices and rules of international organisations aiding the interpretation and application of commercial law.